The role of value innovation capabilities in the influence of market orientation and social capital to improving the performance of Central Kalimantan Bank in Indonesia - Usup Riassy Christa; I. Made Wardana; Christantius Dwiatmadja; Vivy Kristinae (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Research in the field of banking business management during a pandemic requires the cooperation of organizations with the changing business environment. Resources that are able to be managed effectively and efficiently at the Central Kalimantan Regional Bank in Indonesia are thus managed in an effort to support the organization. The key to the bank's performance as an innovative organization lies in the core business values that are strengthened by organizational resources, so that the focus of value innovation becomes the activities that improve business performance as a mediating factor between external and internal factors. Research was conducted on 250 senior employees with quantitative analysis using the Structural Equation Modelling-Partial Least Square (SEM-PLS) statistical tool. It was found that external factors originating from market orientation and social capital significantly improved business performance. The success of the mediation process as a novelty research conceptual research has significant positive results as a core business innovation to improve the business performance of Central Kalimantan regional banks. The research objective is to improve banking performance by collaborating between consumer needs, value innovation and social capital as a trigger for excellent change in Bank Kal-Teng. The value of this research is as a reference for innovating capability value as the main business strategy using information from external factors, so as to improve the bank's business performance as needed.
Keywords: 650; business performance; market orientation; social capital; value innovation capability